Consuming the Reality TV Wedding - Sgroi, Renee (Ethnologies, 2006)
This article investigates the intersection of weddings, the wedding industry, consumption, and reality TV by considering the reality TV series, Trista and Ryan’s Wedding. This show featured the real-life wedding of Trista Rehn and Ryan Sutter, who met on the series The Bachelorette. The author argues that reality TV’s emphasis on the “real,” its narrative techniques (including product assimilation), and the wedding industry’s stress on having a “unique” wedding converge on this show to mobilize consumer fantasies and dreams of the traditional white wedding around specific consumer products. She concludes that examinations of weddings in North American culture must take into account not only the practices and rituals involved in these social and cultural events, but also consider the ways in which popular cultural forms such as reality TV work to produce particular kinds of images.